Analysis of Student Learning Outcomes Assessment in Elementary Schools during the Covid-19 Pandemic: A Survey - Fajri Ismail; Mardiah Astuti (STAI Hubbulwathan Duri, 2022)
This study aims to analyze the implementation of the assessment of student learning outcomes during the Covid-19 pandemic. This study uses a quantitative survey method involving 3 schools in Palembang. Research data collection through surveys containing several questions assisted through Google Forms. Questionnaires distributed with mixed techniques containing questions about the implementation of the assessment, types of assessments, and assessment media. Quantitative data were analyzed by descriptive technique. The results showed that the assessment was carried out comprehensively from knowledge, attitudes and skills or an authentic assessment. The assessment is influenced by student motivation, self-regulation, teacher interaction, assessment instructions, design, infrastructure, and media during implementation. The implementation is supported by internet networks, quotas, assessment applications, smartphones, and laptops.